Evaluasi Pendidikan Islam - Nafisha Aulia, Nisa; Hilmiyati, Fitri; Nugraha, Enung (PT. Cahya Edupreneur Indonesia, 2023)
Evaluation of Islamic Education is an integral approach to assessing, measuring and ensuring the success and quality of education based on Islamic values. This article explores various aspects of evaluation in the context of Islamic education, involving assessments of academic achievement, character development, and the quality of teaching and curriculum. Evaluation is not only interpreted as a mere measurement process, but rather as a dynamic tool that provides constructive feedback. By focusing on evaluation principles, Islamic education can continue to be developed to achieve the main goal: forming individuals with noble character and deep religious knowledge. This article also underlines the important role of evaluation in creating education that is relevant, inspiring and in line with the demands of the times, and emphasizes the need for the involvement of all stakeholders in the evaluation process. With a holistic and continuous approach, evaluation of Islamic education becomes the basis for continuous improvement and positive contribution to society.